2013
DOI: 10.1016/j.ultsonch.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic emulsification of food-grade nanoemulsion formulation and evaluation of its bactericidal activity

Abstract: Basil oil (Ocimum basilicum) nanoemulsion was formulated using non-ionic surfactant Tween80 and water by ultrasonic emulsification method. Process of nanoemulsion development was optimized for parameters such as surfactant concentration and emulsification time to achieve minimum droplet diameter with high physical stability. Surfactant concentration was found to have a negative correlation with droplet diameter, whereas emulsification time had a positive correlation with droplet diameter and also with intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
0
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(191 citation statements)
references
References 36 publications
7
155
0
10
Order By: Relevance
“…After the emulsification, the coefficient of variation of the area of the globules (Figure 1) was calculated. It was observed that the emulsion systems with lower coefficient of variation were more homogeneous and the globules with coefficient of variation of 0.55 and area of 0.01 mm 2 were the most uniform in diameter and distribution, with no aggregation, resulting in HLB of 10 for Brazil nut oil. Microscopic evaluations for the determination of the HLB of vegetable oils have been widely used in the literature, 41 but there are few studies regarding the determination of the area of the globules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the emulsification, the coefficient of variation of the area of the globules (Figure 1) was calculated. It was observed that the emulsion systems with lower coefficient of variation were more homogeneous and the globules with coefficient of variation of 0.55 and area of 0.01 mm 2 were the most uniform in diameter and distribution, with no aggregation, resulting in HLB of 10 for Brazil nut oil. Microscopic evaluations for the determination of the HLB of vegetable oils have been widely used in the literature, 41 but there are few studies regarding the determination of the area of the globules.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Microemulsions have also been identified as potential delivery systems for bioactives in foods, pharmaceutical and cosmetic formulations. 6 There are several types of nanostructures, and microemulsions (MEs) are one of them, that can be used as carriers for lipophilic bioactive compounds, drugs or nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The antimicrobial oil-in-water nanoemulsion was shown to possess a broad spectrum of activity against bacterial pathogens due to the reduced droplet diameter. 11,12 Recently, by our group, the ultrasonic emulsification of eucalyptus oil nanoemulsion was studied, and size reduction was achieved with the aid of ultrasonication time. Also, the stabilized emulsion system was studied for topical application against S. aureus by in vitro and was shown to be nonirritant, and high wound healing activity was observed in Wistar rats in an in vivo experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 3 log (10) CFU/g (99.9%) reductions in L. monocytogenes, S. Typhimurium and E. coli O157:H7 could be obtained after dipping samples in oregano nanoemulsions (0.05% or 0.1%) for one minute and storing samples at 4oC for 72 hr [15]. Diluted food-grade basil oil nanoemulsion showed at least 40% reduction of pure E. coli culture after 60 min [12].…”
Section: Nanoemulsions For Food Decontaminationmentioning
confidence: 96%
“…Compared with conventional emulsions, nanoemulsions have high physical stability, high bioavailability and low turbidity. Therefore, they are attractive systems for food, cosmetics and pharmaceutical industries [12]. They are effective in the inactivation of gram-negative bacteria, bacterial spores, enveloped viruses, and fungal spores [13].…”
Section: Nanoemulsions For Food Decontaminationmentioning
confidence: 99%